The Vapour-Phase Reaction of 2-Alkyltetrahydropyrans with Anilik over Alumina - Richards, Harry (My University, 1952)
The vapour-phase reaction of 2-methy-tetrhydropyran and 2-ethyltetralydropyran with aniline over an activated alumina catalyst has been studied. The product, in each case, consisted of a mature of an N-aryl-piperidine, an N-arylpyrrolidine formed by ring contraction, and two N-alkelnylanilines formed by ring opening. The structures of the nitrogen heterocyclic compounds were established by independent syntheses involving the reaction of the appropriate dibromoalkane with aniline. The N-alkenylanilines were characterised by hydrogenation to known N-alkylanilines and by identification of the osonolysis products.
Keywords: vapour-phase reaction; 2-alkyltetrahydropyrans; aniline; alumina